A silver nanorod based SERS assay for the homogeneous detection of uracil-DNA glycosylase activity. Issue 5 (18th January 2017) - Huang, Yufeng; Liao, Suqi; Xiong, Mei; Ma, Yefei; Zhao, Jingjin; Zhao, Shulin
Abstract : A surface-enhanced Raman scattering (SERS) system for the simple, sensitive and homogeneous detection of UDG activity based on silver nanorods (AgNRs) was developed. Abstract : As an important base-excision repair enzyme, much evidence has shown that uracil-deoxyribonucleic acid glycosylase (UDG) plays a crucial role in maintaining the genomic integrity. This work developed a surface-enhanced Raman scattering (SERS) method for the simple, sensitive and homogeneous detection of UDG activity based on silver nanorods (AgNRs). It utilizes the different adsorption properties of single-strand DNA (ssDNA) and double-strand DNA (dsDNA) on the metal surface. UDG-catalyzed uracil removal from the dsDNA-structured substrate will cause the separation of the substrate into two ssDNA probes which were free to be adsorbed on the AgNR surface. The FAM dye labelled on the substrate would be close to the metal surface, achieving a strong SERS signal. This method is sensitive with a 0.003 U mL −1 detection limit due to the high enhancement factor of AgNRs. The proposed approach also could be used for evaluating the inhibition of UDG activity. This method may have potential applications in UDG-related biological research.